Towards a global alcohol policy: alcohol, public health and the role of WHO - D.H. Jernigan; M. Monteiro; R. Room; S. Saxena
In 1983 the World Health Assembly declared alcohol-related problems to be among the world's major health concerns. Since then, alcohol consumption has risen in developing countries, where it takes a heavy toll. Alcohol-related problems are at epidemic levels in the successor states of the Soviet Union and are responsible for 3.5% of disability-adjusted life years (DALYs) lost globally. Substantial evidence exists of the relationship between the levels and patterns of alcohol consumption on the one hand and the incidence of alcohol-related problems on the other. Over the past 20 years, research has demonstrated the effectiveness of public policies involving, for example, taxation and restrictions on alcohol availability, in reducing alcohol-related problems. In the wake of rapid economic globalization, many of these policies at national and subnational levels have been eroded, often with the support of international financial and development organizations. Development agencies and international trade agreements have treated alcohol as a normal commodity, overlooking the adverse consequences of its consumption on productivity and health. WHO is in a strong position to take the lead in developing a global alcohol policy aimed at reducing alcohol-related problems, providing scientific and statistical support, capacity-building, disseminating effective strategies and collaborating with other international organizations. Such leadership can play a significant part in diminishing the health and social problems associated with alcohol use.